Efektivitas Pembelajaran Daring Dilihat dari Perspektif Guru, Orang Tua dan Siswa di SMA N 20 Jakarta - Titin Supriyatin; Dwi Aprillia Setia Asih (Neolectura, 2021)
This research is designed to analyst the effectivity of online study during the pandemic of covid-19 from diverse perspectives of stakeholders, including teachers, parents and students of 20 Senior High School, Jakarta. This research involves several respondents - 10 teachers, 16 parents and 12 students of 20 Senior High School, Central Jakarta. Descriptive qualitative through the online survey is the method used to indicate the effectivity of online study from respondents’ perspective. In consequence, it results the percentage of the positive and negative impacts of online study.Based on the research analysist, it is assured that online study generates both of impacts to the respondents. The result states that online study is not chained by time and space, meaning students are able to access courses anytime anywhere. It also increases students’ independence. On the other hand, online study has many disadvantages. Teachers and parents have limited access to control the students’ behaviour during the classes because of lacking of time and technology abilities. additionally, it reduces students’ excitement and joy towards the classes.